Is It Worth It? Obesity Affects Snack Food Valuation Across the Menstrual Cycle - Heuberger, Larissa S.; Gobbi, Susanna; Weber, Susanna C.; Graf, Gwendolyn; Tobler, Philippe N.; Asarian, Lori; Geary, Nori; Roth, Mareike; Leeners, Brigitte (Frontiers in Neuroscience, 2022)
Background. The importance of menstrual cycle physiology in appetite and obesity is poorly understood. We investigated the effects of BMI, menstrual cycle phase and sweet and salty taste on monetary valuation of snack foods. Methods. We recruited 72 women and after the application of in- and exclusion criteria 31 participants with healthy weight and 25 with obesity remained. The participants completed a willingness to pay (WTP) task to measure subjective value of 30 snack food items in the preovulatory and mid-luteal cycle phases. Results. Generalized linear mixed model (GLMM) analysis revealed that BMI, cycle phase and snack taste interacted to influence WTP (-0.15 [-0.22,-0.03], p=0.002). Hence, WTP was inversely related to BMI, but the strength of the relation depended on cycle phase and taste. The WTP of participants with healthy weight for salty taste changed across cycle phase but the WTP for sweet was not affected by cycle phase. The cycle effect for the salty snacks ceased in participants with obesity. Conclusions. The inverse effect of BMI on WTP valuation of snack foods contrasts with the positive effect of BMI on pleasantness ratings for milkshakes by the same women that we previously reported. This indicates that the two measures reflect different aspects of food-related valuative processing in obesity. Furthermore, the WTP data suggest that the selection of salty snacks may differ from that of sweet snacks in the preovulatory phase of the menstrual cycle for individuals of healthy weight. The cycle phase does not seem to affect food valuation of participants with obesity. These findings are relevant to understanding and treating obesity in women.